Penyusunan Enterprise Arsitektur SPBE Pada Badan Perencanaan Pembangunan Daerah Dalam Program Perencanaan Pengembangan dan Evaluasi Pembangunan Daerah Provinsi Jawa Barat - Tiofenny Angelina; Asti Amalia Nur Fajrillah; Ridha Hanafi (Jurnal Ilmiah Teknologi Informasi Asia, 2022)
Advances in information technology, in its current form, are closely related to modern society, and the government as a service provider to carry out government missions more openly, effectively and efficiently, as well as to facilitate access. The objective to be achieved from this study is to produce a blueprint design for the Electronic-Based Government Architecture of the West Java Provincial Government in the domains of Business Processes, Data and Information, SPBE Applications, and SPBE Services (Excluding SPBE Infrastructure and SPBE Security). This study has the target of 'The realization of smart, clean and accountable governance innovations'. With aconceptual m odel to make it easier for researchers to explain the concept of the research process from the beginning of the research to the end of the research. Keywords: Information Technology; Governance, SPBE